Therapeutic Garden With Contemplative Features Induces Desirable Changes in Mood and Brain Activity in Depressed Adults - Olszewska-Guizzo, Agnieszka; Fogel, Anna; Escoffier, Nicolas; Sia, Angelia; Nakazawa, Kenta; Kumagai, Akihiro; Dan, Ippeita; Ho, Roger (Frontiers in Psychiatry, 2022)
Therapeutic values of contact with nature have been increasingly recognized. Growing body of evidence suggests that a unique subcategory of “contemplative landscapes” is particularly therapeutic. Previous studies predominantly focused on observational designs in non-clinical populations. It is not known if these effects can be extrapolated to populations suffering from depression and experimental designs need to be utilized to establish causality. We examined the effects of in-situ passive exposure to three urban spaces on brain activity, namely a Therapeutic Garden with high Contemplative Landscape scores (TG), Residential Green (RG) and Busy Downtown (BD), and self-reported momentary mood in adults aged 21-74 (n=92), including 24 clinically depressed and 68 healthy participants. Portable, multimodal electroencephalography (EEG) and functional near-infrared spectroscopy (fNIRS) systems were used to record brain activity and a Profile of Mood States (POMS) questionnaire was used to record mood before and after exposure. We tested the interactions between the site, time and group for the mood, and between site and group for the neuroelectric oscillations and brain hemodynamics. Self-reported pre-post mood was significant only at the TG(p=0.032), in both groups. The lowest Total Mood Disturbance (TMD) was reported at TG and the highest in BD (p=0.026). Results from fNIRS indicated marginally significant lower oxy-Hb in the frontal region at TG as compared to BD (p=0.054) across both groups. The marginally significant effect of site and group was also observed (p=0.062), with the Clinical group showing much lower oxy-Hb at TG than Healthy. The opposite pattern was observed at BD. EEG results showed differences between Healthy and Clinical groups in the Frontal Alpha Asymmetry (FAA) pattern across the sites (p=0.04), with more frontal alpha right in Clinical and more left lateralization in the Healthy sample at TG. Temporal Beta Asymmetry (TBA) analyses suggested that patients displayed lower bottom-up attention than Healthy participants across all sites (p=0.039). The results suggest that both healthy and depressed adults benefitted from exposure to TG, with possibly different pathways of mood improvement. Visiting therapeutic nature with contemplative features may provide valuable support for the treatment of depression in clinical populations and a self-care intervention in non-clinical populations.